Comprehensive Genomic Profiling of EBV-Positive Diffuse Large B-cell Lymphoma and the Expression and Clinicopathological Correlations of Some Related Genes - Zhou, Yangying; Xu, Zhijie; Lin, Wei; Duan, Yumei; Lu, Can; Liu, Wei; Su, Weiping; Yan, Yuanliang; Liu, Huan; Liu, Li; Zhong, Meizuo; Zhou, Jianhua; et al. (Frontiers in Oncology, 2019)
Epstein–Barr virus (EBV)-positive diffuse large B-cell lymphoma (EBV+ DLBCL) is a rare type of lymphoma with a high incidence in elderly patients, poor drug response and unfavorable prognosis. Despite advances in genomic profiling and precision medicine in DLBCL, EBV+ DLBCL remain poorly characterized and understood. We detected 9 EBV+ and 6 EBV negative cases for next-generation sequencing (NGS) and then performed fluorescence in situ hybridization (FISH) and immunohistochemistry to analyze chromosome rearrangement and gene expression in 22 EBV+ and 30 EBV negative cases. The NGS results revealed recurrent alterations in MYC and RHOA, components of apoptosis and NF-κB pathways. The most frequently mutated genes in EBV+ DLBCL were MYC (33.3%), RHOA (33.3%), PIM1 (22.2%), MEF2B (22.2%), MYD88 (22.2%) and CD79B (22.2%) compared with KMT2D (66.7%), CREBBP (50.0%), PIM1 (33.3%), TNFAIP3 (33.3%) and BCL2 (33.3%) in EBV-negative DLBCL. MYC and KMT2D alterations stood out the most differently mutated genes between the two groups. FISH detection displayed a lower rearrangement rate in EBV+ cohort. Furthermore, KMT2D expression was highly expressed and associated with poor survival in both cohorts. MYC was only overexpressed and related to an inferior prognosis in the EBV+ DLBCL cohort. In summary, we depicted a distinct mutation profile for EBV+ and EBV-negative DLBCL and validated the differential expression of KMT2D and MYC with potential prognostic influence, thereby providing novel perspectives into the pathogenesis and precision medicine of DLBCL.